2021
DOI: 10.1016/j.omtn.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA Xist regulates sevoflurane-induced social and emotional impairment by modulating miR-98-5p/EDEM1 signaling axis in neonatal mice

Abstract: Long non-coding RNA (lncRNA) X-inactive specific transcript (Xist) is involved in apoptosis and inflammatory injury. This study aimed to assess the role of lncRNA Xist in sevoflurane-induced social and emotional impairment and neuronal apoptosis in neonatal mice and hippocampal neuronal cells. The performance in social and emotional tests and the expression levels of lncRNA Xist and microRNA (miR)-98-5p after sevoflurane exposure were measured. Moreover, the effects of suppression of lncRNA Xist on neuronal ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The snRNA‐seq strip plot highlighted a large number of special cell‐type genes highly responsive to sevoflurane in the PFC, including several down‐regulated gene expressions ( Itm2b in the glutamatergic neurons, Eif2s3y in the GABAergic neurons, Apoe in the astrocytes, and Ptgds in the oligodendrocytes) and up‐regulated expression of Snhg11 in the microglia, which may represent potential molecular targets for sevoflurane neurotoxicity (Figure 3b). Interestingly, Xist was over‐expressed in almost all cell types, which may lead to sevoflurane‐induced social and emotional impairment (Xu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The snRNA‐seq strip plot highlighted a large number of special cell‐type genes highly responsive to sevoflurane in the PFC, including several down‐regulated gene expressions ( Itm2b in the glutamatergic neurons, Eif2s3y in the GABAergic neurons, Apoe in the astrocytes, and Ptgds in the oligodendrocytes) and up‐regulated expression of Snhg11 in the microglia, which may represent potential molecular targets for sevoflurane neurotoxicity (Figure 3b). Interestingly, Xist was over‐expressed in almost all cell types, which may lead to sevoflurane‐induced social and emotional impairment (Xu et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Sevoflurane (Sev) is one of the most commonly used general anesthetics in pediatric anesthesia due to its advantages of rapid induction, low respiratory irritation, and rapid recovery ( Patel & Goa, 1996 ). Various animal studies have confirmed that repeated exposure to general anesthetics during development can result in long-term cognitive impairment, fine motor injury, and social impairment in mice ( Tang et al, 2021 ; Wu et al, 2020 ; Xu et al, 2021 ; Zhang et al, 2022b ; Zhang et al, 2023 ) and non-human primates ( Neudecker et al, 2021 ). However, many questions regarding the long-term effects of general anesthesia on brain development remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [ 10 ] showed that miR-98-5p could ameliorate neuronal damage induced by oxygen glucose deprivation/reoxygenation (OGD/R). Upregulation of miR-98-5p alleviated sevoflurane-induced social and emotional disorders in neonatal mice [ 12 ]. EphA4 receptors regulate neurogenesis and border formation in the developing brain [ 13 ], and the absence of EphA4 improves neuroinflammation and tissue damage induced by traumatic brain injury [ 14 ].…”
Section: Introductionmentioning
confidence: 99%